A LOT OF VOICES OF TOPOS UKRAINE IN WESTERN UKRAINIAN AND EMIGRANT PROSE OF 20-3O-H YEARS OF THE ХХ CENTURE - Khorob, M. B. (PRECARPATHIAN BULLETIN OF THE SHEVCHENKO SCIENTIFIC SOCIETY Word, 2021)
A review on a monograph is Natalia Martin „Western Ukrainian and emigrant prose of 20 - 30 years of the ХХ centure : paradygm of Reconcist". – Ivano - Francivsc: Pricarpathians national university named by Vasiliy Stefanic, 2008. – 356 s.